Development Of Instagram-Based Educational Media On Personal Hygiene Durung Menstruation - Nur Friza Arta Nadia; Rita Yulifah; Finta Isti Kundarti; Hening Ryan Aryani (Journal of Innovative and Creativity (Joecy), 2026)
Adolescent girls require accessible and engaging health information to support appropriate personal hygiene practices during menstruation. Conventional educational media, including printed comic books, may have limitations in accessibility, interactivity, and alignment with adolescents’ digital media preferences. This study aimed to develop Instagram-based educational media on personal hygiene during menstruation that was relevant, attractive, and understandable for adolescent girls. A Research and Development (R&D) design was employed by adapting the Borg and Gall model into seven stages: standard media evaluation, needs assessment, focus group discussion (FGD), prototype development, expert validation, prototype revision and finalization, and small-group testing. The study involved six students in the needs assessment, seven students and one teacher in the FGD, two experts for material and media validation, and 15 female students in the small-group trial at SMP Negeri 1 Dau, Malang, Indonesia. Data were collected using interview and FGD guidelines and validation questionnaires and were analyzed descriptively using quantitative and qualitative approaches. The developed media combined Instagram feed images and short Reels videos covering menstrual hygiene practices, the menstrual cycle, myths and facts, and six-step handwashing. Material and media experts both provided a feasibility score of 100%, categorized as very eligible. The small-group trial obtained an 83% response, categorized as very positive. The findings indicate that the developed Instagram-based educational media was feasible and positively accepted by adolescent users. Further studies using larger samples, pre- and post-intervention assessments, control groups, and longitudinal follow-up are recommended to determine its effects on knowledge and menstrual hygiene behavior..